The amicus curiae in the field of constitutional justice - Bazán, Víctor (2021)
This study investigates the current profiles of the amicus curiae and its importance in the unfolding of constitutional justice. Also analyzes its usefulness as a tool for citizen participation feasible in the judicial debate around issues of institutional and social interest, and assesses its contribution to qualitative argument acquis domestic and international human rights courts, on the basis of growth interaction spaces Constitutional law, Constitutional Litigation and International Law of Human Rights.